2014
DOI: 10.1159/000368963
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Weight Loss and Maintenance in Overweight/Obese Pediatric Patients

Abstract: Background: Pediatric lifestyle interventions have positive short-term effects on obese patients. Studies on long-term effects are still scarce in Europe. We investigated long-term weight patterns and sociodemographic predictors of a weight change in a large Central European (Germany, Austria and Switzerland) overweight pediatric cohort. Methods: The APV (Adiposity Patients Verlaufsbeobachtung) database was retrospectively analyzed; 157 specialized childhood obesity centers contributed standardized data of 29,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
3
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 32 publications
7
67
3
7
Order By: Relevance
“…The authors also stated a higher success rate in younger children [10]. Similar results were indicated by another study with 2-year follow-up [11]. This emphasizes the importance of an early and effective intervention in childhood obesity.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The authors also stated a higher success rate in younger children [10]. Similar results were indicated by another study with 2-year follow-up [11]. This emphasizes the importance of an early and effective intervention in childhood obesity.…”
Section: Introductionsupporting
confidence: 71%
“…2a-c). Previous studies indicated that a lower BMI at the beginning of a LI is one predictor of success as measured by BMI SDS [10,11]. However, the indication to participate in an outpatient or inpatient LI depends on obesity degree and existing risk factors or comorbidities (table 4) [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at 36 months, 33% had a decrease of at least 5% in BMI SDS and 27% had a decrease of ≥0.25 BMI SDS. This was a very acceptable long‐term outcome when it was compared with many other contemporary studies and even more acceptable when we took into account that only a few studies were able to present long‐term follow‐up data . Our encouraging results on long‐term outcome could be, at least partly, due to good motivation for treatment and adherence to the protocol.…”
Section: Discussionmentioning
confidence: 58%
“…28 An expert panel has suggested that a BMI z-score reduction of 0.20 units is associated with clinically significant improvement. 29 Other studies suggest that changes of 0.15 BMI z-score units led to more healthful cardio-metabolic profiles. 28 As suggested by a recent evidence review of childhood obesity management, regardless of what the threshold of clinical significance will be determined to be, simply arresting gain in excess BMI likely constitutes a clinically important benefit for many children.…”
Section: Discussionmentioning
confidence: 99%